MARKET TO BOOK VALUE, FIRM SIZE, AND THE UNDERPRICING OF INDONESIAN INITIAL PUBLIC OFFERINGS - Singgih, Marmono; Pricilia, Veryantika Putri; Lavista, Eka (Review of Management and Entrepreneurship, 2019)
The focus of this study is to analyse whether market to book value ratio and firm size determine the extent of initial returnrate of firms making initial public offering (IPO). The subject of the study is all IPO from the period of 2007-2016. There are 173 IPOs used as sample. It uses two measurements of initial retuns, the raw return and the market adjusted return. As documented in many studies, there is evidence that on average the Indonesian IPO experience underpricing. Results using regression analysis show that market to bookvalue ratio and firm size have negative and significant effect on both of the measures for initial return. This finding asserts the importance of understanding the market to book value ratio in the valuation of Indonesia IPOs.